Broiler Response on Increase in Flour Leaves Miana (Coleus atropurpureus, L) as a Feed Aditive in Ration - Nelzi Fati; Ramond Siregar; Ulva Mohtar Luthfi; Debby Syukriani; Toni Malvin (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
Increased bacterial resistance to antibiotics provides a great opportunity to obtain antibacterial compounds by utilizing bioactive compounds from biological natural wealth. In Indonesia there are many known medicinal plants. Miana plants (Coleus atropurpureus, L) are one of the potential medicinal plants in Indonesia. This plant is widely used as medicine. This study aims to determine the effect of adding miana leaf flour to the ration on body weight gain, feed consumption, feed conversion and carcass percentage. This study used a completely randomized design with 5 treatments and 4 replications. The treatment was A = control, B = 1% Miana leaf flour / kg ration. C = 2% leaf flour miana / kg ration, D = 3% miana leaf flour / kg ration E = 4% miana leaf flour / kg ration. What was observed were performance and carcass including feed consumption, feed conversion, body weight gain, carcass percentage. The results of this study showed that the addition of miana leaf flour in the ration had no significant effect (P> 0.05) on body weight gain, feed conversion, feed consumption and carcass percentage. Giving miana leaf flour in the ration can be tolerated up to 4% in broiler rations.